Mass Media and Public Policy:Global Evidence from Agricultural Policies - Alessandro Olper; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
Mass media plays a crucial role in infirmation distribution and thus in the political market and public policy making. Theory predicts that infirmation provided by mass media reflects the media's incentives to provide news to different types of groups in society, and affects these groups?influence in policy-making. We use data on agricultural policy from 60 countries, spanning a wide range of development stages and media markets, to test these predictions. We find that, in line with theoretical predictions, public support to agriculture is strongly affected by the structure of the mass media. In particular, a greater role of the private mass media in society is associated with policies which benefit the majority more: it reduces taxation of agriculture in poor countries and reduces subsidization of agriculture in rich countries, ceteris paribus. The evidence is also consistent with the hypothesis that increased competition in commercial media reduces transfers to special interest groups and contributes to more efficient public policies.
Keywords: D72; D83; Q18; 330; Mass Media; Media Structure; Information; Agricultural Protection; Political Economy